2018
DOI: 10.1016/j.aop.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Local quantum uncertainty guarantees the measurement precision for two coupled two-level systems in non-Markovian environment

Abstract: Quantum Fisher information (QFI) is an important feature for the precision of quantum parameter estimation based on the quantum Cramér-Rao inequality. When the quantum state satisfies the von Neumann-Landau equation, the local quantum uncertainty (LQU), as a kind of quantum correlation, present in a bipartite mixed state guarantees a lower bound on QFI in the optimal phase estimation protocol [Phys. Rev. Lett. 110 (2013) 240402]. However, in the open quantum systems, there is not an explicit relation between L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…The quantum speed limit time can be significantly decreased along with the increasing of the environment coupling parameters γ 0 and hopping interaction J, and demonstrates stronger periodic oscillation phenomenon. The similar property can also be found in the dynamics of the quantum correlation [47] based on the skew information [48,49]. For the dynamics of the system, one should notice that it can not be reduced to the damped Jaynes-Cummings model when the hopping interaction J is zero.…”
Section: The Coupled Two-level System-ancilla Interacting With Common...supporting
confidence: 59%
See 1 more Smart Citation
“…The quantum speed limit time can be significantly decreased along with the increasing of the environment coupling parameters γ 0 and hopping interaction J, and demonstrates stronger periodic oscillation phenomenon. The similar property can also be found in the dynamics of the quantum correlation [47] based on the skew information [48,49]. For the dynamics of the system, one should notice that it can not be reduced to the damped Jaynes-Cummings model when the hopping interaction J is zero.…”
Section: The Coupled Two-level System-ancilla Interacting With Common...supporting
confidence: 59%
“…Substituting the quantum state |ψ id (t) into the Schrödinger equation i ∂ t | ψid (t) = H|ψ id (t) , one can obtain the differential equations for the coefficients A id (t), B id (t), C k id (t) and D k id (t) [47]:…”
Section: The Coupled Two-level System-ancilla Interacting With Indepe...mentioning
confidence: 99%
“…It should be noted that in this model, the other steps of the estimation process are assumed to be noiseless. Besides, in (36), it has been shown that for a model, consisting of two qubits interacting with independent non-Markovian environments, when we consider the effects of the environment and the coupling interaction between subsystems, the QFI and LQU do not satisfy the similar relationship generally. Now we investigate whether or not this bound holds for our model including the PM's and the Unruh effect.…”
Section: Lower Bound On Qfi With Lqumentioning
confidence: 99%
“…9(a)-9(d) for determined values of other parameters, equality F ϕ = U A (ρ A,I ) holds. Moreover, inequality (36) refers to the fact that the quantum correlations measured by LQU, are a sufficient resource to ensure that some information about the phase parameter can be extracted from the system in the process of estimation. In addition, for probe quantum states with any nonzero amount of discord, and for M ≫ 1 repetitions of the estimation process, the optimal detection strategy, asymptotically saturating the quantum Cramér-Rao bound, leads to production of an estimator φbest with the following necessarily limited variance:…”
Section: Lower Bound On Qfi With Lqumentioning
confidence: 99%
See 1 more Smart Citation